2022
DOI: 10.1007/s12144-022-03037-7
|View full text |Cite
|
Sign up to set email alerts
|

Parenting dimensions/styles and emotion dysregulation in childhood and adolescence: a systematic review and Meta-analysis

Abstract: Emotion dysregulation is a transdiagnostic factor in the development of various mental and behavioral disorders, thus requiring ample evidence for prevention and intervention approaches. The aim of the current systematic review and meta-analysis was to investigate the association between parenting dimensions/styles and emotion dysregulation in childhood and adolescence. Following the PRISMA guidelines, the review was registered (PROSPERO CRD42021251672) and search terms were entered in Web of Science, Scopus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 114 publications
1
12
0
Order By: Relevance
“…Rather, psychological control was associated with increases in children's reports of their own emotion dysregulation over time, whereas parental support was associated with decreases in teachers' reports of children's emotion dysregulation. These findings correspond to a recent systematic review and meta-analysis, which found that negative parenting-including psychological controlwas associated with greater emotion dysregulation, whereas positive parenting behaviors-including parental support-was associated with less emotion dysregulation (Goagoses et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…Rather, psychological control was associated with increases in children's reports of their own emotion dysregulation over time, whereas parental support was associated with decreases in teachers' reports of children's emotion dysregulation. These findings correspond to a recent systematic review and meta-analysis, which found that negative parenting-including psychological controlwas associated with greater emotion dysregulation, whereas positive parenting behaviors-including parental support-was associated with less emotion dysregulation (Goagoses et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…For instance, in one meta-analysis, the results reveal a small yet significant effect [9]. However, the analysis also suggests a high heterogeneity of current related studies in the field, which may potentially be due to varying conceptualization of ER [9]. Hence, while there is a rich source of studies on this topic, an urgent uniformity of related concepts is also necessary for future studies.…”
Section: Comparative Studies Between Positive and Negative Parenting ...mentioning
confidence: 97%
“…When comparing positive and negative parenting in children's ER, multiple meta-analysis and systematic reviews have raised general trends that positive parenting is negatively related to ER difficulties, whilst negative parenting is positively associated with ER difficulties [10]. For instance, in one meta-analysis, the results reveal a small yet significant effect [9]. However, the analysis also suggests a high heterogeneity of current related studies in the field, which may potentially be due to varying conceptualization of ER [9].…”
Section: Comparative Studies Between Positive and Negative Parenting ...mentioning
confidence: 99%
“…For example, it is known that authoritarian parenting harms children's self-image (Singh 2017). Since children and adolescents are not welcome to express and share their feelings in harsh and authoritarian families, it is more likely that the children of such families have ineffective coping skills and difficulties in emotion regulation (Wolfradt et al 2003, Goagoses et al 2022). In addition, parental psychopathology predisposes children and adolescents to psychopathology through learning processes (e.g., imitation or modeling) or arranging their environments (Dodge 1990).…”
Section: Family and Peer Relationshipsmentioning
confidence: 99%